Early postnatal discharge during COVID-19: A cross-sectional study - Wondyifraw Yeshitila Tesfaye; Bekelu Teka Worku (Women's Health, 2021)
Introduction: Postnatal hospital stay is decreased by 30% during COVID-19 in developed countries. However, there is paucity of data in developing countries. Hence, this study aims to assess the prevalence of early postnatal discharge during COVID-19 in Jimma Health Centers. Methods: Facility-based cross-sectional study was conducted from 1 February to 30 March 2021. Sample was calculated using single population proportion formula and allocated proportionally to the health centers. Data were interred into Epidata version 3.1 and exported to SPSS version 22.0 for analysis. Multivariable regression was done to identify associating factors at p < 0.05. Result: Three hundred ninety women were included into study making a response rate of 96.8%. Early discharge prevalence was 316 (81.0%). Attending elementary school adjusted odds ratio = 0.26 (confidence interval = 0.087–0.798), plan for postnatal care within a week adjusted odds ratio = 0.410 (confidence interval = 0.221–0.760), knowing postnatal maternal danger sign adjusted odds ratio = 0.258 (confidence interval = 0.141–0.473), women adjusted odds ratio = 0.421 (confidence interval = 0.211–0.838), or husband adjusted odds ratio = 0.051 (confidence interval = 0.014–0.186) made decision of discharge were negatively and distance on foot <30 min adjusted odds ratio = 3 (confidence interval = 1.121–8.058) was positively associated with early discharge significantly. Conclusion: This study has identified early postnatal discharge is high which can contribute to reduce the risk of acquiring COVID-19. However, the authors recommend further study to differentiate whether early discharge is due to COVID-19 or other reasons.